HOW TO IMPROVE THE USING OF GENERIC DRUGS? A REVIEW - Nurwigya Mohamad Putri (International Interdisciplinary Conference on Sustainable Development Goals, 2019)
The use of generic drugs in developing countries is still low. This is influenced by people's knowledges, perceptions, and attitudes towards generics which are also still low. Medical advisor and candidate ofmedical advisor need to be given good knowledge of generic drugs that they are expected to provide communication, information, and education actively about generic drugs. In mature healthcare systems, both pharmacists and physicians support the use of generic drugs and offer them to all patients regardless of socioeconomic status. A lack of trust in manufacturers and the quality of the generic drugs affects how pharmacists and physicians consider generic drug use in less mature healthcare systems. The government policy on replacing branded drugs with generic drugs is one solution to increase the use of generic drugs.